Markovian homogeneous on the second component with controlled reducible model of reliability estimation of complex radioelectronic systems - Корнійчук M. T.; Совтус I. K.; Семенченко A. I.; Шутко M. O. (Proceedings of National Aviation University (archive), 1999)
Investigated is the possibility of construction of mathematical stochastic model of reliability of operation process of radioelectronic systems. Markovian chains, homogeneous on the second component are used as the means of increasing the model adequacy